NADİR BİR PLEVRAL EFÜZYON NEDENİ: OVER HİPERSTİMULASYON SENDROMU - TETİKKURT, Cüneyt and Çepni, İsmail and OCAL, Pelin and KOÇAK, Orçun and BARBAROS, Merve (Cerrahpaşa Medical Journal, 2014)
Background and Design.- A 32 year old nulligravida with a 9 year history of infertility presented with dry cough and left pleuritic chest pain. She had undergone a transfer of embryos after an induction of ovulation with follicle stimulating hormone, gonadtropin releasing hormone and human chorionic gonadotropin two weeks ago. Two days after admission dyspnea appeared and chest x-ray demonstrated a moderate left pleural effusion. Spiral CT revealed left pleural effusion with otherwise normal findings. Pleural fluid was a lymphocytic exudate. Pleural biopsy revealed nonspesific inflammatory changes. Plasma estradiol and β-HCG concentrations were 3901 pg/ml and 172 IU/L respectively. Pelvic ultrasonography showed bilateral enlarged ovaries with numerous follicular cysts and ascites compatible with ovarian hyperstimulation syndrome (OHS). Pleural effusion may represent a diagnostic challenge for pulmonary clinician in OHS if the clinical presentation is equivocal.